1985
DOI: 10.1159/000233814
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Immunity: The Immunoregulatory Effect of n-6 Essential Fatty Acids Is Mediated through Prostaglandin E

Abstract: Suppression of cell-mediated immune responses by essential fatty acids (EFA) was demonstrated in mice maintained on a standard laboratory diet for rodents. Daily oral administration of EFA at doses ranging from 125 to 750 mg/kg body weight significantly suppressed local host-versus-graft and graft-versus-host reactions as measured by popliteal lymph node assay. Studies employing immune sera directed against E-type prostaglandin demonstrated that n-6 EFA-induced suppression was mediated through prostaglandin E<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In addition, TGF‐ β knock‐out mice survive for only a few weeks before widespread activation of autoimmune T cells leads to death [34] and targeting TGF‐ β gene deletion to T cells has a similar effect, demonstrating that T cell homeostasis requires TGF‐ β signalling [35]. Prostaglandin inhibitors such as indomethacin augment EAE [36] and prostaglandins of the E series have potent effects on cell‐mediated immunity and EAE [37]. Additionally during the natural recovery phase from EAE, TGF‐ β ‐secreting T cells can inhibit EAE effector cells, TGF‐ β is expressed in the CNS and, in oral tolerance‐induced protection in EAE, TGF‐ β and PGE 2 are expressed in the brain [38–40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TGF‐ β knock‐out mice survive for only a few weeks before widespread activation of autoimmune T cells leads to death [34] and targeting TGF‐ β gene deletion to T cells has a similar effect, demonstrating that T cell homeostasis requires TGF‐ β signalling [35]. Prostaglandin inhibitors such as indomethacin augment EAE [36] and prostaglandins of the E series have potent effects on cell‐mediated immunity and EAE [37]. Additionally during the natural recovery phase from EAE, TGF‐ β ‐secreting T cells can inhibit EAE effector cells, TGF‐ β is expressed in the CNS and, in oral tolerance‐induced protection in EAE, TGF‐ β and PGE 2 are expressed in the brain [38–40].…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the enlargement in popliteal lymph node size is due largely to proliferation of activated host cells; most of these originate within the popliteal lymph node, although there is also some recruitment of cells from the bloodstream. Using this assay, Mertin et al (1985) reported that both the G v. H and H v. G responses were suppressed following a single administration of fish oil concentrate (750 mgkg body weight) by oesophageal catheter to mice before, or immediately after, the innoculation with allogeneic cells. A suppressed H v. G response was observed in mice fed on a 160 g fish oilkg diet compared with those fed on a standard chow diet (Hinds & Sanders, 1993); lower levels of fish oil (25, 50, 100 gkg) did not significantly affect the response.…”
Section: Delayed-type Hypersensitivitymentioning
confidence: 99%
“…Experimentally it has been shown that the n-6 fatty acid abnormalities are reproduced in biotin-deficient chicks and rats, and are reversed after supplementation with the vitamin [17][18][19][20][21][22][23]26] . The changes in the FA spectrum induced by biotin treatment are likely to have many desirable consequences, particularly in the metabolism of PG synthesis [27,28]. PGs, oxygenation products of FAs, may act via several mechanisms: PGE1 has an anti-inflammatory property through its ability to regulate the generation of arachidonic acid, and PGE2 may improve the capacity of the immune system to regulate T-and B-lymphocytic interactions [29].…”
Section: Serum Fatty Acidsmentioning
confidence: 99%